1996
DOI: 10.1128/jvi.70.8.5230-5235.1996
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-4 causes delayed virus clearance in influenza virus-infected mice

Abstract: Two different subsets of T cells, Th1 and Th2 cells, have been demonstrated to secrete different profiles of cytokines and to influence various infections in different ways. Whereas cytokines secreted by Th1 cells, particularly gamma interferon, promote the generation of cell-mediated immunity, Th2 cells and their cytokines (interleukin-4 [IL-4], IL-5, IL-10, and IL-13) have been shown to function in recovery from parasitic infections and in antibody responses. In this study, we analyzed the effects of the dom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
60
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(64 citation statements)
references
References 41 publications
4
60
0
Order By: Relevance
“…In fact, only a few studies have demonstrated IL-4 mediated inhibition of viral replication (Goletti et al, 2002;Lin et al, 2003). Furthermore, expression of IL-4 by recombinant ectromelia virus or vaccinia virus exacerbated infection in vivo and the administration of recombinant IL-4 delayed virus clearance in influenza virusinfected mice (Jackson et al, 2001;Moran et al, 1996;Sharma et al, 1996). In this study, we demonstrate that treatment of Vero E6 cells with IL-4 decreased susceptibility of these cells to SARS-CoV infection by 10-to 100-fold.…”
Section: Discussionmentioning
confidence: 56%
“…In fact, only a few studies have demonstrated IL-4 mediated inhibition of viral replication (Goletti et al, 2002;Lin et al, 2003). Furthermore, expression of IL-4 by recombinant ectromelia virus or vaccinia virus exacerbated infection in vivo and the administration of recombinant IL-4 delayed virus clearance in influenza virusinfected mice (Jackson et al, 2001;Moran et al, 1996;Sharma et al, 1996). In this study, we demonstrate that treatment of Vero E6 cells with IL-4 decreased susceptibility of these cells to SARS-CoV infection by 10-to 100-fold.…”
Section: Discussionmentioning
confidence: 56%
“…10 Rather, treatment of mice with IL-4, a Th2 cytokine, resulted in a signi®cant delay in in¯uenza virus clearance. 11 Dysregulation of CD4 + T-cell function is observed with ageing. While decreased production of and response to IL-2 seems to be a common phenomenon in ageing, 5 IFN-c production in the aged was reported to be lower, 30 show no difference, 31 or be higher 6 than in the young.…”
Section: Discussionmentioning
confidence: 99%
“…10 Furthermore, in vivo treatment with IL-4 suppressed the CTL response and IFN-c production, and delayed viral clearance. 11 IL-1b, IL-6 and tumour necrosis factor-a (TNF-a) levels increase in the early stages of in¯uenza infection and are involved in the initiation of the immune response as well as in the in¯ammatory response. IL-6 is involved in T-cell activation and represents an essential competence factor that synergizes with IL-1 to control the initial steps of T-cell activation, including induction of IL-2 and enhancement of responsiveness to IL-2.…”
Section: Introductionmentioning
confidence: 99%
“…Whereas, Th2 clones are noncytolytic and failed to promote recovery from lethal infection after adoptive transfer (70). Furthermore, in vivo treatment with IL-4 suppressed CTL response and IFN-g production, and delayed viral clearance (71). Only a limited number of studies have investigated the effect of vitamin E on resistance against infections in humans.…”
Section: Vitamin E and Infectionsmentioning
confidence: 99%